The feasibility of daily, weekly and ten-day water-level forecasting in colombia (2010)
This paper analyses the feasibility of forecasting daily, weekly and ten-day water-levels at 20 hydrological stations forming part of the monitoring network supporting the Institute of Hydrology, Meteorology and Environmental Studies’ (IDEAM) Alert Service in Colombia (www.ideam.gov.co). Such viability was determined by a set of orthogonal performance criteria and implementing optimally adaptive linear combinations (OALC) was recommended for this study as a viable operator for configuring a real-time hydrological forecast system. It is shown that the forecast for daily, weekly and ten-day levels had satisfactory viability for 70% of the cases studied.